2017
DOI: 10.1038/srep40630
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations of the N-N Bond Dissociation for the Gas-phase RDX and HMX

Abstract: NO2 fission is a vital factor for 1,3,5-Trinitroperhydro-1,3,5-triazine (RDX) and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) decomposition. In this study, the geometry of the gas-phase RDX and HMX molecules was optimized, and the bond order and the bond dissociation energy of the N-N bonds were examined. Moreover, the rate constants of the gas-phase RDX and HMX conformers, concerning the N-N bond dissociation, were evaluated using the microcanonical variational transition state theory (μVT). The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Because of the low sublimation rate, the dispersed single molecules in the gas state touch the nucleation and grow in the AAA conformation. The work of Vladimiroff and Rice verified that RDX molecular conformations in the gas phase consist of AAE of the α phase and AAA of the β phase. , Moreover, some works also revealed that β-RDX easily transitions into α-RDX upon touching α-RDX or contacting the tip of a needle. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Because of the low sublimation rate, the dispersed single molecules in the gas state touch the nucleation and grow in the AAA conformation. The work of Vladimiroff and Rice verified that RDX molecular conformations in the gas phase consist of AAE of the α phase and AAA of the β phase. , Moreover, some works also revealed that β-RDX easily transitions into α-RDX upon touching α-RDX or contacting the tip of a needle. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Given to the many applications of hydrazine derivatives, it is important to understand the structure–activity relationship of the thermodynamics of N–N bonds, in particular, their strength as measured by using the homolytic bond dissociation enthalpies (BDEs). With the rapid development of quantum chemistry and computers in recent years, the theoretical methods such as composite methods, DFT methods, etc., have become powerful tools for calculating BDEs of organic compounds. For the theoretical studies on N–N BDEs, He and co-workers used ab initio calculations at M06-2X/cc-pvtz level to investigate the N–N BDEs of different conformational 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) in the gas-phase, and the bonding strength was evaluated by the bond order (BO). Reynisson et al calculated the N–N BDEs of the moieties found in drugs by B3LYP method, and the mean N–N BDEs for the six hydrazones and three nitrosamines are 255.4 and 146.7 kJ/mol, separately.…”
Section: Introductionmentioning
confidence: 99%
“…For LLM‐105, the pathways which produce P2+NO through the nitro‐nitrate rearrangement and P1+NO 2 via direct C‐NO 2 bond fission will dominate the decomposition process at low and high temperatures, respectively. The BDE of C‐NO 2 is 72.99 kcal/mol in LLM‐105, while the BDE of N‐NO 2 in RDX is 50.59 kcal/mol 42 . Consequently, the decomposition rate coefficient of RDX is several orders of magnitude faster than LLM‐105 at the same condition.…”
Section: Resultsmentioning
confidence: 94%
“…The BDE of C-NO 2 is 72.99 kcal/mol in LLM-105, while the BDE of N-NO 2 in RDX is 50.59 kcal/mol. 42 Consequently, the decomposition rate coefficient of RDX is several orders of magnitude faster than LLM-105 at the F I G U R E 3 The rate coefficients (s −1 ) of important reaction pathways are presented. The temperature is ranging from 300 to 1500 K and the pressure is ranging from 1 to 100 atm [Color figure can be viewed at wileyonlinelibrary.com] same condition.…”
Section: Rate Coefficientsmentioning
confidence: 99%